Chronic energy deficiency status in pregnant women as a risk of low birth weight - Pertiwi, Mumpuni Intan; Permatasari, Mekar Anggun; Rodliya, Adzka Fahma (Riset Informasi Kesehatan, 2025)
Abstract Background: The condition of pregnant women with chronic energy deficiency (CED) could cause bad influence on mothers and children such as delivering infant with low birth weight (LBW). In 2020 the proportion of CED in Surakarta was 4,16% and experienced increase compared to 2019. The highest LBW case in Surakarta was obtained in work area of Pajang Pajang Health Center with case proportion 2,8%. The CED status is included into maternal factor of LWB because of insufficient nutrition of mothers and infants.This study aim to find out the status of CED on pregnant women towards the risk of LBW. Method: Analytic observational research with case control design retrospective approach using secondary data of Pajang Public Health Center in 2020. The research samples consisted of case sample with total sampling technique and control sample comparison 1:2 until obtained case sample 25 and control sample 50. Results: The result of chi-square showed that p-value 0.005 and odd ratio = 4,935. Conclusion: Pregnant women with CED has risk of 4,935 times higher to give birth with LBW compared to pregnant women with no CED.